Evaluation Study of the Implementation of Flexible Working Arrangement in Public Sector Organization during Covid-19 Pandemic - Tasrin, krismiyati; Wahyuadianto, Agus; Pratiwi, Pratiwi; Masrully, Masrully (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2021)
The studies of Flexible Working Arrangement (FWA) have increased significantly in 2020. However, most studies are focused on the benefits and risks of FWA in general or particular jobs. The model of FWA implementation in different characteristics of jobs to improve performances are still insufficiently researched. Using a case study with qualitative and quasi-statistic data, this study investigates the Indonesian public sector in implementing FWA policy. Investigating Indonesia allows the researchers to describe how FWA in a mandated leading training institute promotes performances in different types of jobs. This study finds that each department endured unique circumstances. The Research Department could apply for full FWA due to employees’ high work autonomy, sufficient work equipment, adequate individual competency, compatibility for virtual communication, and high satisfaction while working at home. The Training Department had a similar level of readiness even though many of its staff preferred work at the office. Meanwhile, the Competency Assessment Department was bound to categorize tasks based on their possibility to be accomplished at home or office before applying FWA, due to its transition toward the e-assessment system. Finally, the Administration Department needed extra effort before applying FWA, which included out-of-office work-objects accessibility for its employees, paid special attention to competency gap among employees particularly IT skills, and overcame limited work equipment at home. Above all, organizations are required to focus on performance management notably in tasks distribution, work supervision, feedback, and maintenance of trust between employees and the management team.